P691 Disparate care: rates of treat to target among patients with inflammatory bowel disease. (30th January 2023) - Haydek, J; Oonk, A; Cheng, D; Ahmed, W; Click, B; Fennimore, B; Gerich, M; Hou, J; Scott, F
Abstract: Background: Inflammatory bowel diseases (IBD) therapies are limited by low response rates and risks of loss of response. Treat to target (T2T) algorithms aim to maximize the benefit of therapies by establishing a framework for assessing patient reported outcomes, biochemical evaluation (C-reactive protein (CRP) or fecal calprotectin (FC)), and structural assessment via endoscopy or enterography. There are limited data on adoption rates of T2T in real-world clinical practice. We aimed to describe rates of T2T utilization in a large regional medical system in the United States. Methods: A retrospective cohort study was conducted from 2015-2021. Individuals with IBD starting a new biologic therapy were identified. Collected data included demographics, laboratory data, current medications, and procedure and imaging data. Patients were categorized based on whether they completed T2T, defined as CRP or FC testing at 2-4 months after starting a new therapy, and structural assessment, defined as colonoscopy, sigmoidoscopy, capsule endoscopy, or enterography within 6-12 months after starting a new therapy. Complete adherence was defined as both of these criteria being met. Social deprivation index (SDI), with higher values associated with higher rates of social deprivation, was derived using mail codes. T-tests, Pearson chi-square tests, ANOVA and multivariable logistic regression were used for comparisons. Results: 7, 962 patients were identified (Table 1). Rates of T2T were low; only 7.81% of patients completed biochemical monitoring at 2-4 months (0.83% FC, 8.65% CRP, 1.76% both), 9.80% completed structural assessment, and 3.43% completed both. In univariable logistic regression, higher age (OR 0.98, p<0.01), IBD type (UC OR: 0.69, p<0.01), having no insurance (OR 0.84, p=0.02) and low social deprivation index (SDI) (OR 1.004, p<0.01) were associated with lower T2T completion rates. In multivariable logistic regression, ulcerative colitis (UC), younger age, and lower SDI score were significantly associated with likelihood of completing any T2T (Table 2). When considering biochemical monitoring at 2-4 months, Asian race, UC diagnosis, age, SDI score and year were significantly associated with completion (Table 3). UC diagnosis, year and age were significantly associated with completion of structural assessment (Table 4). Conclusion: Treat to target completion rates among patients with IBD starting biologic therapies were low in this large cohort. Age and UC diagnosis were negatively associated with completing T2T. Social deprivation score was positively associated with biochemical monitoring. Further research is required to understand barriers to T2T monitoring.